Profil Berpikir Kritis Siswa Asperger pada Pembelajaran Bangun Datar dengan Metode Montessori - Dyah Ayu Sulistyaning Cipta; Donna Avianty; Anik Kurniawati (Universitas Syiah Kuala, 2019)
Critical thinking skills in Mathematics learning are commonly only centred on typical students. Sometimes teachers forget that there are students with special needs who also need to study Mathematics; one of them are students with Asperger's Syndrome. Through this study, the researcher used the Montessori method to teach the plane geometry topic. The research method used was descriptive qualitative. The students observed were two students with Asperger's learning while applying the Montessori method. This study illustrated how the Montessori method was used to students with Asperger's syndrome and described the profile of students critical thinking suffering from Asperger's syndrome. The instruments in this study were the critical thinking test and field notes conducted by the research team. The results showed that the Montessori method seemed to make students with Asperger's Syndrome more expressive and willing to interact with the surrounding environment. They also had better motor skills and the critical thinking skills of the students were of high criteria. Besides, the aspects of freedom, integrating with the environment and the presence of playground tools, seem to make the Montessori method appropriate to be used use by students with Asperger's Syndrome.